Kantian Relationship between “Moral Law” and Virtue: Separation or Companionship - Rahime Çetin (Felsefe Arkivi)
Time and again, virtue has been explained as the principal factor behind a good human life. “Virtue,” as a chosen way of living or as a human trait, is an important research subject. In the history of ethical philosophy, Kant has been an influential figure, who has elucidated many ethical dilemmas. His conception of ethics was built on a set of universally applicable moral principles that were based on the guiding belief of practical rationality, or “Categorical Imperative,” and “virtue” isnot seen as an inherent quality of human nature. This study will attempt to show that both sides of the arguments purport to establish that Kant is not a classical virtue ethicist because he does not establish a virtue-based ethics or that he is a virtue ethicist since virtue has an important place in his ethics and has flaws. In accordance with this purpose, the definitions, expressions, and the concept of the “highest good” (summum bonum) and the duties of virtue with respect to the concept, as found in the Doctrine of Virtue (a chapter in The Metaphysics of Morals), will be discussed to arrive at a clearer understanding of the significance and status of the notion of virtue.